2014
DOI: 10.1007/s00396-014-3328-3
|View full text |Cite
|
Sign up to set email alerts
|

PLA maleation: an easy and effective method to modify the properties of PLA/PCL immiscible blends

Abstract: In this study, maleic-anhydride-grafted polylactide (PLA-g-MA) was investigated as a potential compatibilizing agent for the polylactide (PLA)/poly(ε-caprolactone) (PCL) system, with the aim of enhancing the final properties of the two polymer blends. Indeed, PLA-g-MA was prepared via reactive blending through a free radical process and characterized by means of 1 H-NMR and titration measurements, which demonstrated that the employed procedure allows grafting 0.7 wt% of MA onto the polymer backbone, while avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 34 publications
5
47
0
2
Order By: Relevance
“…1, which is also in agreement with previous studies (Castillo et al 2010;Dell'Erba et al 2001;Gardella et al 2014;Harada et al 2008;López-Rodríguez et al 2006). In order to explain this kinetic enhancement, the limited miscibility of PCL and PLA chains was suggested as the underlying mechanism (Sakai et al 2009;Zhang et al 2013).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…1, which is also in agreement with previous studies (Castillo et al 2010;Dell'Erba et al 2001;Gardella et al 2014;Harada et al 2008;López-Rodríguez et al 2006). In order to explain this kinetic enhancement, the limited miscibility of PCL and PLA chains was suggested as the underlying mechanism (Sakai et al 2009;Zhang et al 2013).…”
Section: Resultssupporting
confidence: 84%
“…The close solubility parameters of PCL and PLA, 9.2 and 10.1 (cal/cm 3 ) 1/2 , respectively (Coleman et al 1990), and the lack of specific interactions between PCL and PLA leads to partial miscibility of their blends (López-Rodríguez et al 2006). The miscibility of PLA/PCL blends can be enhanced by using compatibilizers, which modify the interfacial properties either chemically or physically (Castillo et al 2010;Gardella et al 2014;Harada et al 2008;Salehiyan and Hyun 2013;Shin 2013;Tuba et al 2011). The compatibilized blends have shown better mechanical properties such as elongation at break and impact resilient compared to virgin PLA.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, this improvement is limited by the low compatibility of PLA/PCL blends. Therefore, efficient compatibilizer for PLA/PCL blends has been intensively asked [28][29][30][31]. Less care has been paid to study effect of the properties of the component, and mixing and processing conditions on the morphology of PLA/PCL blends [32].…”
Section: Introductionmentioning
confidence: 99%
“…Gardella et al [93] proposed the maleic anhydride grafted poly(lactic acid) (PLA-g-MA) as effective compatibilizer of PLA/PCL blends. It was found that replacing of PLA by PLA-g-MA reduced dimensions of the PCL domain and enhanced their adhesion to PLA, which have beneficial impact on the mechanical properties (increasing the elongation at break without deterioration of Young's modulus) of PLA/ PCL blends.…”
Section: Aliphatic Polyesters Blendsmentioning
confidence: 99%